(untitled) - Nash, Laura L. (Boston, Mass., 2009)
The process begins with 12 basic questions What is needed is a process of ethical inquiry that is immediately comprehensible to a group of executives and not predisposed to the utopian, and sometimes anticapitalistic, bias marking much of the work in applied business philosophy. First step is a set of 12 questions that draw on traditional philosophical frameworks but that avoid the level of abstraction normally associated with formal moral
Keywords: Business ethics,Đạo đức kinh doanh